Peningkatan Kinerja Guru dalam Pelaksanaan Pembelajaran Melalui Supervisi Klinis Di Uptd Sd Negeri 04 Taeh Bukik Kabupaten Lima Puluh Kota Tahun 2021 - Wirdatis Wirdatis (Journal on Education, 2022)
The implementation of supervision by the principal must be carried out continuously considering that improving teacher performance cannot be done instantly. As a supervisor, the principal must be able to understand the characteristics and conditions of each teacher so that what is the essence or purpose of supervision can be achieved. In addition, the principal must also be able to plan, implement, and follow up on the results of the supervision. In general, the purpose of this study was to examine the implementation of clinical supervision by the principal at the UPTD SD Negeri 04 Taeh Bukik, Lima Puluh Kota Regency. This research was carried out in two cycles, each cycle having two meetings. The stages of each cycle are planning, implementation, observation, and reflection. The principal as an educational leader has a very large role in developing the performance of school teachers. Principals in an effort to improve teacher performance, must be able to help teachers achieve the shared goals that have been set. Assistance to teachers in carrying out these tasks, can be done through the implementation of educational supervision. Educational supervision puts emphasis on the process of forming and developing teachers' professional abilities, which begins with making improvements in the way teachers teach in the classroom, in this way it is hoped that students can learn well, so that teaching goals can be achieved optimally. The principal as a supervisor is expected to be able to carry out his duties by supervising the learning process of teachers in the classroom, in order to improve the professional abilities of teachers which is reflected in the ability to manage the learning process of teachers in the classroom, which includes: mastering subject matter in terms of mastering the field of study or subjects he/she holds, plans learning programs, implements and leads/manages the learning process, assesses the progress of the learning process.